2017
DOI: 10.1051/0004-6361/201730647
|View full text |Cite
|
Sign up to set email alerts
|

Normal and counter Evershed flows in the photospheric penumbra of a sunspot

Abstract: Context. The Evershed effect, a nearly horizontal outflow of material seen in the penumbrae of sunspots at the photospheric layers, is a common characteristic of well-developed penumbrae, but is still not well understood. Even less is known about photospheric horizontal inflows in the penumbra, also known as counter Evershed flows. Aims. Here we present a rare feature observed in the penumbra of the main sunspot of AR NOAA 10930. This spot displays the normal Evershed outflow in most of the penumbra, but harbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 47 publications
8
56
1
Order By: Relevance
“…In contrast, the superstrong fields reported by Siu-Tapia et al (2017) (> 7 kG based on SPINOR 2D inversions) were observed in the tails of inverted penumbral filaments carrying a counter-EF (CEF), i.e. a gas inflow towards the sunspot umbra at photospheric heights, near the inner penumbral boundary.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, the superstrong fields reported by Siu-Tapia et al (2017) (> 7 kG based on SPINOR 2D inversions) were observed in the tails of inverted penumbral filaments carrying a counter-EF (CEF), i.e. a gas inflow towards the sunspot umbra at photospheric heights, near the inner penumbral boundary.…”
Section: Introductionmentioning
confidence: 89%
“…For the SPINOR 2D inversions used in this work (cf. Siu-Tapia et al 2017) all the atmospheric free parameters were initially defined at three optical depth nodes, placed at log(τ) = −2, −0.8, and 0. This set of optical depth nodes was shown to work well for the inversion of Hinode/SP observations of sunspots by Siu-Tapia et al (2017).…”
Section: Observations and Spatially Coupled Inversionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Counter Evershed flows were also found in umbral filaments (e.g., Kleint & Sainz Dalda 2013), during the formation of penumbrae (Schlichenmaier et al 2012;Romano et al 2014;Murabito et al 2016Murabito et al , 2018, and over stable penumbrae (Louis et al 2014;Siu-Tapia et al 2017). Lim et al (2011) presented observations of two granular-like features (GLFs), about 1 ′′ wide, at the tip of penumbral filaments and associated with MMFs.…”
Section: Discussionmentioning
confidence: 99%